Diseases and access to treatment by the Peruvian prison population: an analysis according to gender - A Hernández-Vásquez; C Rojas-Roque
ABSTRACT Objective: In Peru, prisons are spaces with overcrowding, deteriorated infrastructure, poor sanitary conditions and difficult access to medical treatment. The objective of this study is to estimate the burden of disease and access to treatment for different morbidities in the Peruvian inmate population. Methods: An analysis of secondary data of the First National Penitentiary Census (PCNP) 2016 in Peru was carried out. The absolute frequencies and percentages of each self-reported health condition, the presence of a diagnosis of a disease before entering the prison system and access to treatment were obtained. Results: 74,130 inmates were included in the analysis. The most common diseases in prisons are depression (9.6%), anxiety (8.6%), chronic lung disease (8.4%) and arterial hypertension (6.9%). All diseases included, with the exception of hepatitis, have a diagnostic before the incarceration of less than 60%. Access to medical treatment was higher in women than in men and in general, mental health illnesses had low access to medical treatment. Conclusions: Chronic and infectious diseases are frequent in those deprived of liberty, with mental health problems being more prevalent in women. In general, access to treatment is low, especially in men and for mental health illnesses. This situation reflects the need to develop intervention programs that promote health and increase the universality of health care in those deprived of liberty.